Thailand revealing perspective - Kiengsiri, Pensri 1931-; Kiengsiri, Narudee (Bangkok, Thailand Khumson Books Thailand, 1994)
Author's recollection about the Thai customs and social life.
Thailand yesterday and today -- The choosing of Thai names -- The significance of the Thai folktales -- Cock fighting in Thailand -- Bull fighting in South Thailand -- A Thai theatre-sala chalerm Thai -- The fight of Thai novelist -- A Thai S.E.A. write awardee -- Traditional Thai ghosts -- Thai proverbs.
Keywords: Thailand -- Social life and customs